Dual band infrared detection method based on mid-infrared and long infrared vision for conveyor belts longitudinal tear. (May 2018) - Yu, Binchao; Qiao, Tiezhu; Zhang, Haitao; Yan, Gaowei
Highlights: Mid-infrared and long infrared visions are integrated together in the DBID method. The DBID method is not limited by dark and dusty environment. The existing tear or scratch can be detected by mid-infrared vision. Tearing precursor can be detected by long infrared vision. Abstract: In mining operation, the longitudinal tear detection of conveyor belt is of great significance to safety production. A novel method, named Dual Band Infrared Detection (DBID), is proposed to detect the longitudinal tear of conveyor belts in this paper. The DBID method is based on the collaboration of mid-infrared and long infrared vision. The DBID sensor device captures the lower surface images of conveyor belt. The feature of tear or scratch and tearing precursor can be extracted by analyzation of captured images. The DBID method is verified by experiments and practice, including the capturing of dual band infrared images (mid-infrared and long infrared images), image preprocessing, and tear detection. The DBID method is not only unlimited by visual condition, but also much more accurate and reliable compared with the Integrative Binocular Vision Detection (IBVD) method presented before which meets the requirement of real-time online detection.